2021
DOI: 10.1101/2021.03.26.437250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tribbles 2 confers enzalutamide resistance in prostate cancer by promoting lineage plasticity

Abstract: Second-generation anti-androgen, such as enzalutamide (Xtandi), is commonly prescribed for prostate cancer therapy, but enzalutamide-resistant, lethally incurable disease invariably develops. To understand the molecular basis of enzalutamide resistance, we comprehensively analyzed prostate tumors and clinically relevant models. These studies revealed that enzalutamide resistant prostate cancer cells overexpress Tribbles 2 (Trib2), a pseudokinase. Expression of Trib2 is negatively regulated by androgen receptor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Another interesting study has revealed the role of Tribbles 2 (Trib2), a pseudokinase, in mediating antiandrogen resistance in prostate cancer. They found that antiandrogen treatment-resistant cells overexpress Trib2 which can induce lineage switching by upregulation of SOX2 and BRN2 [ 123 ].…”
Section: Cellular and Lineage Plasticity In Cancermentioning
confidence: 99%
“…Another interesting study has revealed the role of Tribbles 2 (Trib2), a pseudokinase, in mediating antiandrogen resistance in prostate cancer. They found that antiandrogen treatment-resistant cells overexpress Trib2 which can induce lineage switching by upregulation of SOX2 and BRN2 [ 123 ].…”
Section: Cellular and Lineage Plasticity In Cancermentioning
confidence: 99%